Athapascan woman and children, Yukon River area, Alaska, 1908 - University of Washington Libraries
Woman with scarf on head and shawl over shoulders carries an infant in sling on her back, and is followed by a small girl in scarf, ruffled cloak, dress & decorated moccasins. Log building in background. Caption on image: Indians of Yukon. No. 9, copyright 1908. C L Andrews